Anodizing—Interplay between bath aging and oxide formation and properties. (1st October 2018) - Schneider, Michael; Kremmer, Kerstin; Gierth, Uta
Abstract : The present study investigates the interplay between ongoing bath aging during the anodizing process and the formation and properties of the anodic formed oxide layers on AA 1050 in sulfuric acid. The change in the bath over the time of use is studied by controlling the conductivity of the bath. The pH value and the concentration of Al 3+ ions in the bath are simultaneously measured. The kinetic of the oxide formation depending on the bath aging is electrochemically investigated by repetitive potential controlled anodizing of reference samples. Supplementary material diagnostics by SEM and infrared reflection–absorption spectroscopy show a significant decrease of the oxide film thickness as well as the molecular composition with ongoing bath aging.